A Corpus-Based Study On The Use Of Reporting Verbs In Applied Linguistics Journal Articles Published From 2020-2024 - Adrianto Ramadhan; Weningtyas Parama Iswari; Aridah (E3L: Journal of English Teaching, Linguistic, and Literature, 2025)
Reporting verbs are essential in academic writing because they help convey the writer's stance, attitude, and relationship with the reader, as highlighted in corpus-based research. This research was a corpus-based study that investigated the use of reporting verbs in applied linguistics journal articles published between 2020 and 2024. The main objectives were to identify the categories of reporting verbs used in the articles and determine the most frequently used categories within this period. This research applied a corpus linguistic technique, which used quantitative methods. The study specifically focuses on the frequency of reporting verbs in journal articles published within the selected time period. A corpus of 316 articles from the Indonesian Journal of Applied Linguistics was used as a data for the analysis. The data was processed using the software tool AntConc 4.2.0, which allowed for a detailed examination of the reporting verb frequencies and their categorization. The results revealed that Discourse Acts were the most frequently used reporting verbs, followed by Research Acts and Cognition Acts. Within the Discourse Acts category, the "certainty" subcategory emerged as the most prevalent.